Genetic diversity of chondrostereum purpureum (Pers.) pouzar causing silverleaf disease on blueberries in Chile - Rojo, Carmen (2017)
Blueberry (Vaccinium corymbosum L.) in Chile is being affected by silver disease whose causative agent is Chondrostereum purpureum (Pers.) Pouzar. This fungus causes a decrease in the yield of the fruit and the death of the plant. So far, this disease has not been reported in the literature attacking blueberry plants in Chile. The main objective of this research was to characterize genetically the populations of Ch. purpureum at molecular level using the ITS-RFLP markers. The results of the ITS-RFLP indicate a low level of diversity in the Chilean populations of Ch. purpureum. When analyzing the isolates collected in blueberry, two large groups were configured in the dendrogram. The first one grouped 49 isolates with the same molecular profile and in the second cluster there was a greater diversity among the isolates. On the other hand, when we analyzed Ch. purpureum isolates collected in other hosts, 12 isolates constituted a group with identical molecular profile with the 49 isolates collected from blueberry. Analysis of variance of the molecular data showed that there were no statistical differences between Ch. purpureum collected in different areas or in different hosts.